2019
DOI: 10.2147/ott.s215400
|View full text |Cite
|
Sign up to set email alerts
|

<p>Silencing Of MAGI1 Promotes The Proliferation And Inhibits Apoptosis Of Glioma Cells Via The Wnt/β-Catenin And PTEN/AKT Signaling Pathways</p>

Abstract: Background: Membrane-associated guanylate kinase (MAGUK) with inverted orientation protein 1 (MAGI1) is a novel member of the MAGUK family with a vital role in tumor progression related to invasion and metastasis. However, the function of MAGI1 in glioma is currently unknown. We therefore analyzed the expression of MAGI1 protein in human glioma samples, glioma cell lines and glioma stem cells (GSCs), and explored its effects on glioma cell proliferation and apoptosis. Methods: MAGI1 expression in glioma tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Some studies have indicated that in estrogen receptor-positive breast cancer, MAGI1 is a new potential tumor suppressor gene (Alday-Parejo et al, 2020). Via the Wnt/β-Catenin and PTEN/AKT signaling pathways, MAGI1 silencing inhibits apoptosis of glioma cells and promotes proliferation (Lu et al, 2019). Moreover, by regulating PTEN, MAGI1 curbed the invasion and migration of HCC (Zhang and Wang, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that in estrogen receptor-positive breast cancer, MAGI1 is a new potential tumor suppressor gene (Alday-Parejo et al, 2020). Via the Wnt/β-Catenin and PTEN/AKT signaling pathways, MAGI1 silencing inhibits apoptosis of glioma cells and promotes proliferation (Lu et al, 2019). Moreover, by regulating PTEN, MAGI1 curbed the invasion and migration of HCC (Zhang and Wang, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The downstream target genes of miR-484 was predicted using MIRDB, MAGI1 with the highest score was chosen to forsubsequentresearch. Some studies indicated that, in estrogen receptor positive breast cancer, MAGI1 is a new potential tumor suppressor gene [29].Via the Wnt/β-Catenin and PTEN/AKT signaling pathways, MAGI1 silencing inhibited apoptosis of glioma cells and promoted the proliferation [30]. Moreover, via regulating PTEN, MAGI1 curbed invasion and migration of HCC [31].Our study con rmed that MAGI1 was the downstream target gene of miR-484, and TMEM220-AS1 released MAGI1 through competitive binding of miR-484, thereby regulating the progression of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies performed in glioma cells showed similar outcomes; the study of Lu et al demonstrated that MAGI1 played an essential role during glioma progression; its silencing in different glioma cell lines enhanced proliferation and inhibited apoptosis, increased Wnt/β-catenin signaling, enhanced AKT phosphorylation, and reduced E-cadherin and PTEN expression. Conversely, overexpression of MAGI1 significantly inhibited tumor growth in vivo [57]. Another study found that overexpressing MAGI1 inhibits proliferation, migration, and invasion of glioma cells by regulating cell growth and EMT through AKT, matrix metalloproteinase 2 (MMP2) and MMP9, and the E-cadherin/N-cadherin/vimentin pathway [58].…”
Section: Magi1 Role As Tumor Suppressormentioning
confidence: 99%